Swimming against the stream: the fishbowl discussion method as an interactive tool for medical conferences: experiences from the 11th European Lupus Meeting - Mucke, Johanna; Anders, Hans-Joachim; Aringer, Martin; Chehab, Gamal; Fischer-Betz, Rebecca; Hiepe, Falk; Lorenz, Hanns-Martin; Schwarting, Andreas; Specker, Christof; Voll, Reinhard E.; Schneider, Matthias (Annals of the rheumatic diseases, 2019)
Based on both historical development and functional advantages, such as in emergencies, hierarchical aspects dominate all levels of medicine. Doubtlessly, the high degree of respect for experts and their opinions may impede exchange between different levels of hierarchy. At medical conferences, discussions usually take place between experts, while patients, young doctors and students only listen and rarely actively participate. - - For the 11th European Lupus Meeting in Düsseldorf in March 2018, we have tried the fishbowl method to increase participation at all levels. Fishbowl is an interactive and dynamic technique with a group of discussants sitting in an inner circle that contains an additional empty chair and surrounded by the audience in an outer circle.1 The empty chair can be occupied by any member of the outer circle at any time to join the discussion immediately. After the additional discussant of the auditorium has made his/her statement, he or she will leave the chair again to create an opportunity for another member of the audience (figure 1). - - - - Figure 1 - The fishbowl method. A group …